The Perspective of Value Creation Company: Value Creation and Measurement - Saxena, Ashish K. (Journal of Global Economy, Business and Finance, 2024)
Value seems to be an ever - present term, major problem is there is no clear definition with respect to all business perspectives. Marketing people define it differently, finance team’s definition is different and operations and HR people will define it completely different. Success of any commercial activity is driven by its strategies related to product markets and financial markets. In both the spheres the theme that drives decision making for a company would be its ability to create value. This research article aims to throw light on creation of value by a company and measuring it using various methods.